2019
DOI: 10.1007/s12028-019-00870-w
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Antioxidant Consumption as Early Markers of Neurosurgery-Related Brain Injury in Children

Abstract: Background and Aims Lipid peroxidation represents a marker of secondary brain injury both in traumatic and in nontraumatic conditions-as in major neurosurgical procedures-eventually leading to brain edema amplification and further brain damage. Malondialdehyde (MDA), a lipid peroxidation marker, and ascorbate, a marker of antioxidant status, can represent early indicators of this process within the cerebrospinal fluid (CSF). We hypothesized that changes in cerebral lipid peroxidation can be measured ex vivo fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…(Huang et al., 2022; Li et al., 2019) A defence mechanism consisting of antioxidant enzymes, including SOD, GSH and GSH‐Px, participates in preventing oxidative stress‐induced injury. (Tang et al., 2017) Lipid peroxidation is a marker of secondary brain injury in non‐traumatic and traumatic conditions, (Piastra et al., 2020) and MDA, its final product, is thought to contribute to brain injury. (Su et al., 2020) The SOD and GSH‐Px levels were markedly decreased in a rat model of neonatal hypoxic‐ischaemic brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…(Huang et al., 2022; Li et al., 2019) A defence mechanism consisting of antioxidant enzymes, including SOD, GSH and GSH‐Px, participates in preventing oxidative stress‐induced injury. (Tang et al., 2017) Lipid peroxidation is a marker of secondary brain injury in non‐traumatic and traumatic conditions, (Piastra et al., 2020) and MDA, its final product, is thought to contribute to brain injury. (Su et al., 2020) The SOD and GSH‐Px levels were markedly decreased in a rat model of neonatal hypoxic‐ischaemic brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…TBI is a major traumatic disease, and its incidence is increasing year by year with the development of the economy and transportation [19,20]. Previous research has shown that neuron-inflammation and oxidative stress are the main mechanisms of neuron-degeneration in TBI [21,22]. Here, we demonstrated that inhibition of SNHG1 eased inflammation, oxidative stress and neuronal apoptosis in while 156 downregulated) around the cortex of mice after TBI, and these changes are related to inflammation and immune activity, metabolism and vascular network [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The PN anion can react with carbon dioxide (CO 2 ) to form nitrosoperoxycarbonate (ONOOCO 2 -), which decomposes to form NO 2 · and carbonate (CO 3 -) radicals. [ 38 ] The propylene group in the polyunsaturated fatty acid on the plasma membrane has a double bond structure such that 1 electron in the carbon-hydrogen bond is pulled to 1 side, and the distance between the paired electrons increases, so it is vulnerable to the attack of reactive oxygen molecules, and active lipids (L·) are produced. [ 39 ] L· can react with O 2 to form LP free radicals (LOO·), acquire adjacent H, generate LOOH and a second L·, initiate a chain reaction, and destroy the integrity of the plasma membrane.…”
Section: Pathological Changes Of Mitochondria After Spinal Cord Injurymentioning
confidence: 99%